A Case Study on Giant Malignant Phyllodes Tumor of the Breast - Silva, Catarina Abreu; Moura, Madalena Souto; Afonso, Mariana Gomes; Rodrigues, Susana Lopes; Silva, Ana Catarina (Highlights on Medicine and Medical Science Vol. 5, 2021)
Phyllodes tumor is a rare fibroepithelial tumor of the breast that account for less than 1% of all breast neoplasms [1]. Clinically, it is typically a large, smooth and fast-growing mass that forms from the periductal stroma of the breast [2]. Phyllodes tumor can be considered benign, borderline, or malignant and the percentage of malignant tumors ranges from 23 to 50%. This classification depends on histologic features, as the degree of stromal cellularity and atypia, mitotic count and stromal overgrowth [2]. In this review, we aim to characterize the main clinical and radiological findings of the phyllodes tumors, as well as the anatomopathological findings. We report a case of a huge malignant phyllodes tumor in a 62-year old woman who presented with a large breast mass with 10-month disease evolution time. The patient underwent total mastectomy and the pathology analysis revealed a malignant tumor.